Wybrane obszary zarządzania łańcuchem logistycznym - Wincewicz, Marta (Selected Problems of Logistic Chain Management, 2005)
The article tells about main, chosen by author, comprehensions connected by using the Logistic Chain in the corporation's managing, as such: reasons of the creations the Logistic Chain, the logistic alliance, influences of the internationalization and globalization and the consequences of multicultural management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 173-179